Communication Experiences of Conscious Indonesian Patients Who Underwent Mechanical Breathing in an Intensive Care Unit: A Phenomenological Approach - Fathonah, Septiana; Ernawati, Eka; Hakim, Mohamad S. (Jordan Medical Journal, 2024)
Background: Mechanical ventilation is equipment used by patients in ICU. These patients may experience stress due to inadequate communication, including psycho-emotional pressure with a tendency to depression, anxiety, and frustration. It is important to facilitate effective communication during mechanical ventilation to monitor these patients. Nursing staff need to understand patients regarding their inability to communicate. The installation of mechanical ventilation is a barrier to nurse-patient communication. The culture in which a person lives has an impact on their health-related attitudes and behaviors. Thus, this study aims to determine the experience of the communication needs of conscious patients with experience of mechanical ventilation in ICU. Methods: The research method uses qualitative research with a phenomenological approach. The population in this study were former ICU patients with experience mechanical ventilation who were conscious. The sampling of informants was carried out using a purposive method. This study involved three research informants of various ages. This research was conducted in Yogyakarta, a province of Indonesia. Data collection used in-depth interviews. Data analysis in this study used the Colaizzi method to generate themes. Results: The themes obtained in this study were experience of discomfort disturbance in mechanically ventilated conscious patients; mechanically ventilated patients' communication perceptions; the need for social interaction when mechanically ventilated; and the beliefs experienced by patients while unconscious in ICU. We found a new insight that trusting something the patient has experienced is something that needs to be respected. When patients were unconscious, all participants experienced a spiritual journey that brought them into a state of belief about the dying phase. Conclusion: Communication between patients and nurses is beneficial in providing better nursing care following patient needs. This communication is also needed for patients with mechanical ventilation in ICU. It shows the importance of communication between mechanically ventilated patients and nurses in ICU.